Students’ Silence in EFL Classroom: Contributing Factors and Identities - Rahmi, Rahmi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
Investigating the issue of students' silence is essential since it is considered to discourage students from actively participating in the teaching and learning process. Students’ silence has been investigated from a variety of angles. Nonetheless, there has not been any discussion of EFL students' silence regarding their identities in the Indonesian context yet. Therefore, this study aimed to investigate the factors that influenced the students’ silence in the EFL classroom and the identities that they constructed during the period of silence. To reach the objectives, a qualitative approach was employed. Five students studying English in an English skill class at a university in Aceh participated in this study. The data were collected through classroom observations and semi-structured interviews. The results of this study show that four factors influenced the students’ silence, including being threatened with the presence of classmates or lecturers, being in a too silent class, a lack of comprehension of the studied material, and a lack of confidence. Furthermore, the findings also reveal that the students formed multiple identities during the period of their silence in their EFL classes. The identities underwent development, shaping, and reshaping. This study provides a new insight that, beyond their silence, the students actually actively constructed their multiple identities.